New 2,6,9-trisubstituted purine derivatives as Bcr-Abl and Btk inhibitors and as promising agents against leukemia - Bertrand, Jeanluc; Dostálová, Hana; Krystof, Vladimir; Jorda, Radek; Castro, Alejandro; Mella, Jaime; Espinosa-Bustos, Christian; María Zarate, Ana; Salas, Cristian O (Bioorganic chemistry, 2020)
Bcr-Abl and Btk kinases are among the targets that have been considered for the treatment of leukemia. Therefore, several strategies have focused on the use of inhibitors as chemotherapeutic tools to treat these types of leukemia, such as imatinib (for Bcr-Abl) or ibrutinib (for Btk). However, the efficacy of these drugs has been reduced due to resistance mechanisms, which have motivated the development of new and more effective compounds. In this study, we designed, synthesized and evaluated 2,6,9-trisubstituted purine derivatives as novel Bcr-Abl and Btk inhibitors. We identified 5c and 5d as potent inhibitors of both kinases (IC50 values of 40 nM and 0.58/0.66 μM for Abl and Btk, respectively). From docking and QSAR analyses, we concluded that fluorination of the arylpiperazine system is detrimental to the activity against two kinases, and we also validated our hypothesis that the substitution on the 6-phenylamino ring is important for the inhibition of both kinases. In addition, our studies indicated that most compounds could suppress the proliferation of leukemia and lymphoma cells (HL60, MV4-11, CEM, K562 and Ramos cells) at low micromolar concentrations in vitro. Finally, we preliminarily demonstrated that 5c inhibited the downstream signaling of both kinases in the respective cell models. Therefore, 5c or 5d possessed potency to be further optimized as anti-leukemia drugs by simultaneously inhibiting the Bcr-Abl and Btk kinases.
Keywords: Signal Transduction; Purine derivatives; Agammaglobulinaemia Tyrosine Kinase; Humans; Antineoplastic Agents; QSAR; Btk inhibitors; bcr-abl fúzní proteiny; Quantitative Structure-Activity Relationship; leukemie; protinádorové látky; proteinkinasa BTK; signální transdukce; Docking; puriny; Purines; Leukemia; kvantitativní vztahy mezi strukturou a aktivitou; Fusion Proteins, bcr-abl; lidé; Bcr-Abl inhibitors; buňky K562; K562 Cells